2015
DOI: 10.1093/jrr/rrv042
|View full text |Cite
|
Sign up to set email alerts
|

Validation of64Cu-ATSM damaging DNA via high-LET Auger electron emission

Abstract: Radioactive copper (II) (diacetyl-bis N4-methylthiosemicarbazone) (Cu-ATSM) isotopes were originally developed for the imaging of hypoxia in tumors. Because the decay of a 64Cu atom is emitting not only positrons but also Auger electrons, this radionuclide has great potential as a theranostic agent. However, the success of 64Cu-ATSM internal radiation therapy would depend on the contribution of Auger electrons to tumor cell killing. Therefore, we designed a cell culture system to define the contributions to ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 29 publications
3
50
0
Order By: Relevance
“…RBE values were demonstrated to increase as LET increases in wild-type cells, while this association between LET level and RBE value was not observed in V3 cells. It was confirmed that radiosensitivity is dose-dependent in NHEJ-deficient cells but not LET-dependent, as was previously demonstrated (17,19). Therefore, disruption of NHEJ repair may not be the optimum strategy for the enhancement of tumor control using high LET radiation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…RBE values were demonstrated to increase as LET increases in wild-type cells, while this association between LET level and RBE value was not observed in V3 cells. It was confirmed that radiosensitivity is dose-dependent in NHEJ-deficient cells but not LET-dependent, as was previously demonstrated (17,19). Therefore, disruption of NHEJ repair may not be the optimum strategy for the enhancement of tumor control using high LET radiation.…”
Section: Discussionsupporting
confidence: 85%
“…For monoenergetic beam irradiation, 13 and 70 keV/µm C ions, and 200 keV/µm Fe ions, were used. Monoenergetic C ions with an LET of 70 keV/µm were obtained by Lucite attenuation (17). For OptiCell (Thermo Fisher Scientific, Inc.) irradiation, C ions were accelerated to 290 MeV/n initial energy and spread out with a ridge filter to produce an SOBP of width 6 cm (18).…”
Section: Methodsmentioning
confidence: 99%
“…The additional emission of Auger electrons associated with the electron capture decay canal (electron capture, 43.075%) might considerably contribute to the possible therapeutic effectiveness of this radionuclide. Auger electrons have low kinetic energies and short-range penetration but concomitantly high linear-energy transfer (33), like heavier particles (34,35). The present study might provide the basis for evaluating the radiation safety of 64 CuCl 2 and estimating the dose absorbed by organs at risk in the case of theranostic application.…”
Section: Discussionmentioning
confidence: 84%
“…Carbon ions were accelerated at 290 MeV/nucleon of initial energy and spread out with a ridge filter for 6 cm width of SOBP. The monolayer cell culture was irradiated at the center (50 keV/µm of average LET) within the SOBP at a distance of 119 mm from the entrance (27). Monoenergetic protons that were accelerated to 70 MeV using the NIRS-930 cyclotron have a LET value of 1.0 at the irradiated position.…”
Section: Methodsmentioning
confidence: 99%